Teachers’ attitudes toward integrating internet technology in English language classes - Bolandifar, Saeideh; Noordin, Nooreen; Babashamsi, Parastoo; Shakib, Nahid (International Journal of Language Learning and Applied Linguistics World, 2013)
Today, integrating computer and internet technology in classrooms has had a great influence on educational environments. Based on presence of information technology in the education system of Malaysia, the present study was designed to explore the attitudes of Malaysian English as a second language (ESL) teachers toward integrating the internet technology in English language classes. In addition, it aimed to find out motivating and preventing factors that led these teachers to use or not to use technology in their teaching process. Five Malaysian ESL teachers were selected randomly to take part in the study. In order to get in-depth information, a semi-structured interview was conducted. The analysis of data gathered from interviewing with teachers revealed that Malaysian teachers showed positive attitudes toward internet usage in general, but because of some reasons they utilized it rarely in their teaching. Lack of internet access and computer facilities, insufficient computer skills, and lack of time was reported as obstacles to integrate internet in the classrooms. These findings suggested some implications for policy-makers to help teachers to integrate internet technology in their classrooms.